Offspring body condition and immunocompetence are negatively affected by high breeding densities in a colonial seabird: A multiscale approach - Tella, Jose Luis (2001)
Why avian colonies vary in size and how food competition among nearby colonies affects offspring quality are still not completely understood. We simultaneously examined the effects of four scales of breeding density on two measures of offspring viability (body condition and T-cell-mediated immunity) in the colonial Magellanic penguin. Body condition of fledglings was inversely correlated with breeding density within 100 m2 of nests, and decreased with increasing numbers of breeding pairs competing within the parental foraging ranges (100 km), probably as a result of density-dependent food depletion. The T-cell-mediated immune response was positively correlated with body condition, reflecting, to some extent, the previous breeding-density effects, and was negatively correlated with colony size, which may be related to social stress. However, given the effect of protein intake on cell immunity, this result could also indicate a thus far neglected cost of coloniality, namely the consumption of low-protein food to compensate for the depletion of optimal prey. These results were not influenced by other traits, nor by the current exposure of birds to parasites and diseases, as measured by serological variables. Since body condition and the T-cell-mediated immune response of fledgling birds are indicators of their survival and recruitment prospects, the costs we have identified can explain variability in colony size in relation to food competition with surrounding colonies, as well as the skewed distribution toward small colonies in this species.